Pengaruh variasi sudut terjunan terhadap unjuk kerja pompa hydram (hydraulic ram pump) - R. Sutanto; K. Wardani; M. Wirawan; S. Salman (Universitas Mataram, 2019)
Water is one of the factors which very important and necessary in the life of living creatures. Therefore, water must be available whenever and wherever in the quantity, timing, and sufficient quality. Hydraulic Ram Pump (Hydram) is a pump does not require external energy as the power source. The purposes of this research are understanding the influence of falling angle from the hydrant pump toward generated debit and finding the influence of the falling angle of the hydrant pump to generated efficiency. This research uses hydrant pump by the specification of tube compressor its’ diameter 3 inches and a height 60 cm. the falling angle of pump are 35°, 40°, 45°, 50° and 55°. The falling-height is 1 meter with five variations of weight-lift 3, 3½, 4, 4½, and 5 meters. The method of analysis is conducted by analyzing data obtained during the experiment, where the results in the form of quantitative data which is presented in type of tables and displayed in graphical form. The results of the research shows that the best output debit on falling 35 ° namely 0.079 L / s with 3 meters’ water weight-lift, while the lowest output debit on falling 55 ° namely 0.010 L / s 5 meters’ water weight-lift. The best efficiency is 6.103% in the falling angle of 35 ° with 3 meters’ of water weight-lift, while the lowest efficiency is 1.239% in the falling angle of 55 ° with 5 meters’ of water weight-lift.